Immune responses to Helicobacter pylori infection - Moyat, Mati (Baishideng Publishing Group Inc, 2014)
Helicobacter pylori (H. pylori) infection is one of the most common infections in human beings worldwide. H. pylori express lipopolysaccharides and flagellin that do not activate efficiently Toll-like receptors and express dedicated effectors, such as γ-glutamyl transpeptidase, vacuolating cytotoxin (vacA), arginase, that actively induce tolerogenic signals. In this perspective, H. pylori can be considered as a commensal bacteria belonging to the stomach microbiota. However, when present in the stomach, H. pylori reduce the overall diversity of the gastric microbiota and promote gastric inflammation by inducing Nod1-dependent pro-inflammatory program and by activating neutrophils through the production of a neutrophil activating protein. The maintenance of a chronic inflammation in the gastric mucosa and the direct action of virulence factors (vacA and cytotoxin-associated gene A) confer pro-carcinogenic activities to H. pylori. Hence, H. pylori cannot be considered as symbiotic bacteria but rather as part of the pathobiont. The development of a H. pylori vaccine will bring health benefits for individuals infected with antibiotic resistant H. pylori strains and population of underdeveloped countries.